Russians' "impressionable years": Life experience during the exit from communism and Putin-era beliefs - William Pyle (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This article links Russians' individual experiences during the late-Gorbachev and early-Yeltsin years to the beliefs those same individuals espoused in the Putin era, over a decade later. Drawing on questions, some of which are retrospective, from the first wave of the Life in Transition Survey, I show that a range of attitudes - including diminished support for markets and democracy and stronger support for reducing inequality - can be explained by whether an individual suffered labor market hardships (wage cuts, arrears, and/or unemployment) in the half decade from 1989 to 1994. More recent labor market disruptions, surprisingly, bear no such relationship to beliefs in 2006. Relative to the rest of the former Soviet Union, this pattern is unique. Though an explanation is difficult to pin down, one speculative hypothesis is that Russians were uniquely impressionable during this exit-from-communism period. Individual economic hardship, in conjunction with the dissolution of the Soviet Union, may have been particularly disorienting for those living in the country in which communism first took root. Life experiences during these years of instability, uncertainty, and diminished status may have left a uniquely deep and enduring impression.
URN:NBN:fi:bof-202007082231
Keywords: A13; J60; P23; P26; P52; 330; social preferences; beliefs; labor market; transition; Russia; Life in Transition Survey